Interpretation and Application of the Convention on the Prevention and Punishment of the Crime of Genocide in the Recent Practice of the International Court of Justice - Rozhets, Anhelina; Hrebenets, Iryna (Vilnius University Open Series, 2024)
The article “Interpretation and application of the Convention on the Prevention and Punishment of the Crime of Genocide in the recent practice of the International Court of Justice”, written by Iryna Hrebenets and Anhelina Rozhets, summarize the recent practice of genocide cases of ICJ, find its main points and how it reflects in international law system. It was defined that the topic of genocide can not be discussed without an emotional approach to it, paying attention to the substance of the Genocide Convention – its universality of participation, binding states and not individuals. It was defined the main aim of the Convention – prevention of genocide, stopping of committing it, and punishment for guilty parties. In that point of view, it could not be placed any reservations in practice, as they would contradict the aims of the Convention. The peculiarity of punishing the state for genocide actions is the obligation to prove the connection between individuals who committed genocide and state’s financial involvement or awareness of committed actions with the specific intent to destroy in whole or in part, a national, ethnic, racial, or religious group. The interpretations of the Convention proved the possibility of the effective fulfilment of erga omnes obligations, related to the prevention of genocide by the third and not directly related states. As the ICJ is the only legal forum that has the opportunity to interpret the Genocide Convention, thus, how it applies and interprets the Genocide Convention – shows how international law reflects the changes in the world order. Today it can be seen the results of it in the ongoing case Ukraine v. Russia, where the last acquisitions are applied in practice.
Keywords: -